(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper deals with the notions of upper and lower slightly α(τ_1,τ_2)-continuous multifunctions. Furthermore, several characterizations of upper and lower slightly α(τ_1,τ_2)-continuous multifunctions are discussed.